Effectiveness of Bay Leaves (Syzygium polyanthum) to Reduce Body Mass Index Among Pre-Menopausal Obese Adults in South Jakarta Regency - Syamsiah, Siti; Indrayani, Triana; Munjanah, Yuliani (JURNAL INFO KESEHATAN, 2024)
Perimenopause is a transition phase towards menopause which is characterized by hormonal changes, including a decrease in the production of the hormone estrogen and an increase in belly fat which can cause obesity. This study aimed to examine the effectiveness of bay leaves to reduce body mass index (BMI). The research design used was quasi-experimental with a one-group pretest and posttest-only design. The population in this study were pre-menopausal adults with obesity who were selected using purposive sampling with a total respondents 30 adults. During 14 days, they are given the 4-5 bay leaves which were previously boiled with around 250 ml water. The BMI was calculated before and after giving the intervention. Data analysis used the Wilcoxon analysis test. The results revealed that there are significantly reduced BMI compared to before and after the intervention. The content of bay leaves can accelerate weight loss in pre-menopause because it has a thermogenic effect on the body and can be used as an alternative herbal therapy that is very easy to obtain and economical which can be used by obese women in perimenopause. The health promotion to introduce bay leaves could be started as bay leaves are easy to find and grow.